Internal Audit During a Pandemic: Acceptance of Technology in Internal Audit in Retail Companies - Ihrom Caesar Ananta Putra; Fangli Zeng; Zainul Hasan; Angga Ade Permana (ABM: International Journal of Administration, Business and Management, 2022)
This research is qualitative research with a case study approach to the use of technology in the internal audit department of a retail company during the pandemic. The samples used were all internal auditors of PT Sumber Alfaria Trijaya Tbk Branch Jember. The data analysis used was the focus group discussion (FGD) method and literature study. Research results related to audit activities during a pandemic from the point of view of technology utilization have been implemented in five (5) sectors. Sector planning, documents, field audits, confirmation and reporting. In general, the use of technology in carrying out internal audits during a pandemic has been well adapted.